Removal of arsenic compound in Yarmouk, Jordan and Zarqa Rivers, Jordan by coagulation and ion-exchange adsorption - Alshwayatt, Kulthum Ahmad Mohamad
The present of arsenic in environment and human life has become an anxiety due to its poisonous and environmental hazards. Long term contact to arsenic can give the consequences to human health and environmental life. There are many studies addressed the techniques for arsenic removal from water which can reduce the impacts to human health and environment. Jordan is one of the countries facing this problem and sought solutions to reduce arsenic in water. This environmental problem occurred for long time without any serious action taken by the government and authority body. Hence, this study aims to determine the arsenic contamination level in Jordan, Zarqa and Yarmouk Rivers and to study the performance of treatment techniques that are coagulation and ion-exchange processes for arsenic removal. In this study, 54 water samples were collected from three Jordan Rivers (Zarqa, Jordan and Yarmouk) from the up-stream, middle-stream and down-stream of the river. Then, the collected samples were analyzed to determine the arsenic contamination level. The coagulation and ion-exchange techniques were used for arsenic removal. The graphite furnace atomic absorption (GF -AAS) was used to analyze the level of arsenic concentration in each step of the process before to coagulation, after coagulation and after ionexchange. The chemical treatment experiments for coagulation and ion-exchange techniques were carried out at different operating parameters such as pH, type and weight of coagulant and speed of mixing. The results of GF-AAS showed that Zarqa River recorded the highest value of arsenic concentration of about 69.81 ppb before coagulation, 57.00 ppb after coagulation and 12.10 ppb after ion-exchange. Meanwhile, the Jordan River showed the 44.23 ppb before coagulation and 34.00 ppb after coagulation and 7.4 ppb after ion-exchange of arsenic content. In addition, the clean river, Yarmouk River showed the concentrations of 7.00 ppb before coagulation, 5.91 ppb after coagulation and 2.61 ppb after ion-exchange. At the mixing speed of 30 rpm, the arsenic concentration was reduced to 39.10 ppb in Jordan, 6.80 ppb in Yarmouk and 65.88 ppb in Zarqa Rivers. Besides, the used MgSO4 also found demonstrated better results compared to (A1SO4)3 and FeC13. Moreover, the experimental results also revealed that the natural zeolite in the ion-exchange process is more effective compared to resin type for arsenic removal. In comparison, both chemical techniques we found to perform to about 20% and up to 89% of arsenic removal for coagulation and ion-exchange, respectively. In conclusion, the concentration of arsenic compounds in Yarmouk, Jordan and Zarqa rivers in Jordan was succe fully examined. The used coagulationdan ion exchange adsorption achieved arsenic removal efficacy up to 90%. Statistical analysis proved that the experimental data are reliable and the both techniques used (coagulation and ion exchange) is totally practical and economic processes to be used for arsenic removal in Jordan's river.